Smartband for Heartbeat and Oxygen Saturation Monitoring with Critical Warning to Paramedic via IoT - I Dewa Gede Hari Wisana Wisana; Priyambada Cahya Nugraha; Farid Amrinsani; Fani Ferina Sani; Yusita Indhira Anwar; Satheeshkumar Palanisamy (Jurnal Teknokes, 2022)
There are vital signs in the human body that indicate important physiological values for the body. In the COVID-19 pandemic, some of the important vital signs that must be monitored are BPM (Beats Per Minute) and SpO2 (oxygen saturation) as indicators of whether a person is in good health or lacks oxygen to predict the early symptoms of COVID-19. The purpose of this study is to create a device on the patient's wrist that can monitor BPM and SpO2 in real-time, as well as provide notifications on smartphones and emails when the patient's condition is abnormal. The contribution of this study is to implement an IoT (Internet of Things) system using a Wi-Fi connection so that monitoring activities are not separated by distance and time. The MAX86141 sensor is used in the design of this tool to detect the BPM and SpO2 values, after which the data is processed and displayed on the ESP32 TTGO T-Display. Monitoring results are also sent to the Blynk, and if the patient's condition is abnormal, an email notification is sent. According to the tool testing results, BPM has the smallest error of 0.94 percent and the largest error of 6.48 percent, whereas SpO2 has the smallest error of 0.20 percent and the largest error of 3.23 percent. The findings of this study can be used to improve the ease and efficiency of body health monitoring activities. This has the potential to significantly improve public health service quality, particularly during the COVID-19 pandemic